Penerapan Model Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV di SDN 3 Namang - Kardela; Fandi Nugroho; Erika Fitri Wardani (Jurnal Riset Multidisiplin Edukasi, 2025)
The low learning outcomes of students in the IPAS subject in class IV SD Negeri 3 Namang are due to the conventional learning method that is still being used, which does not involve students directly in the learning practice. This old-fashioned learning method makes IPAS learning unattractive and boring for students. There is a need for change in implementing learning using the Discovery Learning method. The research question is whether the application of the Discovery Learning method in IPAS lessons can improve student learning outcomes. The purpose of this research is to determine whether the application of the Discovery Learning method can improve student learning outcomes. This research uses Classroom Action Research. Data analysis is carried out using quantitative descriptive methods. The results show that the application of the Discovery Learning model is effective in significantly improving student learning outcomes. The average learning outcome obtained through tests in the first cycle was 50%, and in the second cycle, there was an increase in the average learning outcome to 76.66%. The conclusion that can be drawn is that the application of the Discovery Learning model can improve the learning outcomes of fourth-grade students at SD Negeri 3 Namang.